How Do Intermediary Organizations Support SMEs to Enhance their Absorptive Capacity? - Ansari Vaghef, Alireza; Dornberger, Utz (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2020)
Researchers have discussed intermediary organizations as the crucial facilitators of technology transfer in an innovation system. They employed the intermediary term in different settings in the innovation system literature. In past decades, scholars highlighted the importance of intermediaries repeatedly. However, few studies examine intermediaries’ role in the innovation system. In this paper, we underline the significant role of intermediaries in boosting absorptive capacity in small and medium-sized enterprises by introducing a framework that expresses intermediaries' functions and their services in absorptive capacity as an essential element of successful knowledge and technology transfer.